2015
DOI: 10.1098/rsbl.2014.1007
|View full text |Cite
|
Sign up to set email alerts
|

Animal personality as a cause and consequence of contest behaviour

Abstract: We review the evidence for a link between consistent among-individual variation in behaviour (animal personality) and the ability to win contests over limited resources. Explorative and bold behaviours often covary with contest behaviour and outcome, although there is evidence that the structure of these 'behavioural syndromes' can change across situations. Aggression itself is typically repeatable, but also subject to high within-individual variation as a consequence of plastic responses to previous fight out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
87
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 56 publications
6
87
1
Order By: Relevance
“…Empirical studies, across a range of species, have demonstrated consistent between-individual differences in aggressiveness, characterized by its repeatability over time and across situations (reviewed in Briffa, Sneddon, & Wilson, 2015). Aggression has been defined as overt behaviour that is intended to inflict physical damage to another (reviewed in Nelson & Trainor, 2007).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Empirical studies, across a range of species, have demonstrated consistent between-individual differences in aggressiveness, characterized by its repeatability over time and across situations (reviewed in Briffa, Sneddon, & Wilson, 2015). Aggression has been defined as overt behaviour that is intended to inflict physical damage to another (reviewed in Nelson & Trainor, 2007).…”
mentioning
confidence: 98%
“…Aggression has been defined as overt behaviour that is intended to inflict physical damage to another (reviewed in Nelson & Trainor, 2007). In the context of animal contests, aggressiveness has recently been mentioned as the propensity of an individual to use agonistic behaviour that could include initiating a contest, escalating a contest and attacking an opponent (glossary of Briffa et al, 2015). Intuitively, one might predict that a more aggressive individual may be more likely to win against a less aggressive opponent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, availability of resources will drive the motivation to fight, the likelihood of engaging in a fight being inversely proportional to the availability of resources and proportional to the value of the contested resource unit [16]. Second, individuals might vary in aggressiveness and highly aggressive individuals should experience more fights than those with lower levels of aggression [53].…”
Section: (C) Variation In Skillmentioning
confidence: 99%
“…Our first review was published earlier this year on 'Animal personality as a cause and consequence of contest behaviour' [8]. To date, we have published five reviews, and we intend to maintain a flow of review papers at the rate of approximately one per month.…”
mentioning
confidence: 99%